The Capital Asset Pricing Model Overviewed - Boďa, Martin; Kanderová, Mária (Dyskusja o modelu wyceny aktywów i pasywów, 2009)
One of the dogmas of contemporary financial risk management comprises the assumption that the returns of an asset can be modelled as linearly dependent on the risk-free rate and the market returns; and the resulting Capital Asset Pricing Model (CAPM) has gained great popularity. The contribution focuses upon the CAPM and discusses its appropriateness, with attention being paid to validity of the model.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 66, s. 48-56